Female Breadwinner Families : Their Existence, Persistence and Sources - Robert William Drago; David Black; Mark Wooden (Institute for the Study of Labor (IZA), 2004)
We develop a typology for understanding couple households where the female is the major earner – what we term female breadwinner households – and test it using data from the first two waves of the HILDA Survey. We distinguish temporary from persistent female breadwinner households and hypothesise, and confirm, that these two groups diverge on demographic, socio-economic status (SES), labour market and family commitment characteristics. Among the persistent group we further distinguish those couples where the dominance of a female earner is related to economic factors and those where it appears associated with a purposeful gender equity strategy. We again hypothesise and confirm that these household types significantly diverge, finding that men in the economic group exhibit low SES, poor labour market position, and low levels of commitment to family, while both the women and men in the equity type often achieve positive outcomes regarding gender equity and economic and family success.
Keywords: J16; J12; 330; dual-earner couples; female breadwinners; family structure; gender-role ideology; HILDA Survey; longitudinal data; Haushaltseinkommen; Geschlecht; Frauenerwerbstätigkeit; Haushaltsökonomik; Familienökonomik; Australien